A IMPLEMENTATION OF MIXED METHODS SEQUENTIAL EXPLANATORY DESIGN IN THE PROMOTION MIX OF EDUCATIONAL SERVICES - R. Hozin Abdul Fatah; Hera Noorhernawati; Ricky Hermayanto (LKP DCI, 2024)
This research aims to determine and analyze the implementation of the promotion mix at SMK Plus YSB Suryalaya Tasikmalaya, to find out the decision making in choosing a school at SMK Plus YSB Suryalaya Tasikmalaya and to find out the influence of the promotion mix on the decision making to choose a school at SMK Plus YSB Suryalaya Tasikmalaya. The methodology used in this research is a mixed methods approach/ mixed methods sequential explanatory design , data collection techniques using observation techniques, in-depth interviews and documentation, while the data analysis techniques used in this research are data collection, data processing, data reduction, data presentation and Drawing conclusions. The implementation of the promotion mix carried out by SMK Plus YSB Suryalaya uses Advertising , Sales promotion , Public Relations , Direct Marketing and Personal Selling . The research results show that the five promotion mixes partially or simultaneously influence the decision to choose a school at SMK Plus YSB Suryalaya.